Melacak Implikasi Politik Pendidikan Kolonial Belanda Terhadap Pendidikan Islam: Sebuah Tinjauan Historis - AJMAIN, MAFTUH (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2024)
This essay aims to put light on the effects of Dutch colonial education politics on Islamic education. This research finds numerous implications for the existence of Islamic education in Indonesia using a historical point of view. Both positive as well as negative aspects might be used to analyze these implications. The movement to modernize Islamic education is one of its beneficial elements. While the growth of dualism in Indonesia's national education system is a disadvantage.